Effect of time-weighted average 25(OH)D on the occurrence of major adverse kidney events in IgA nephropathy—from a 10-year population-based cohort study - Fang Lu; Chang Liu; Dandan Song; Li Qian; Jingfeng Zhu; Jingjing Wu; Chengning Zhang; Zhimin Huang; Ming Zeng; Bin Sun; Bo Zhang; Suyan Duan; et al. (Frontiers in Nutrition)
BackgroundVitamin D (VD) deficiency has been found to be common and associated with a higher risk of adverse outcomes in chronic kidney disease (CKD), according to certain studies. However, whether it is associated with the progression of IgA nephropathy (IgAN) and the efficacy of supplementation remains a topic of debate.MethodsA total of 866 patients with IgAN were included. Identification of the baseline and time-weighted average (TWA) serum 25-hydroxyvitamin D (25(OH)D) levels associated with the major adverse kidney events (MAKE) was performed using Kaplan–Meier survival analysis, receiver operating characteristic (ROC) curves, and multivariate logistic regression analysis. Furthermore, the dataset was divided into derivation and validation cohorts using a 6:4 ratio. Internal validation was performed to assess the added value of TWA 25(OH)D levels to clinical variables using ROC curves, decision curve analysis, and Net Reclassification Improvement (NRI). An integrative analysis combining genomic, single-cell RNA sequencing (scRNA-seq), and molecular docking analysis was employed to elucidate the potential mechanism of VD supplementation on the progression of IgAN.ResultsDuring a median follow-up of 4.3 years (interquartile range (IQR): 3.3–5.9 years), a total of 92 (10.6%) patients experienced MAKE. Cumulative renal outcomes were significantly higher in patients with lower baseline and TWA 25(OH)D levels. The multivariate Cox regression analyses indicated that TWA 25(OH)D level was an independent determinant for MAKE in IgAN after adjusting for important confounders. Moreover, it showed reliable predictive performance in risk stratification of MAKE, with the optimal predictive cut-off value of 44.8 nmol/L. Accordingly, a significant linear association was observed between TWA 25(OH)D and the risk of MAKE. Reclassification further confirmed the consistency of the overall findings. Furthermore, in addition to routinely used clinical parameters, the TWA 25(OH)D-based model demonstrated strong risk-prediction power, verified internally, and showed satisfactory efficacy and significant net advantages. Moreover, VD treatment may improve prognosis by regulating the processes of cell chemotaxis, inflammatory response, and defense response through targeting the expressions OF NFKB1 and NR4A1 in proximal tubule cells in IgAN.ConclusionOur findings provide a more comprehensive insight into VD in IgAN and strengthen the efficacy of VD supplementation in IgAN. The long-term maintenance of optimal VD levels from early in life might be associated with reduced future risk of kidney progression in IgAN.